ANALYSIS OF THE CURRENT STATE, TYPES, AND STYLES OF MEN’S SHIRTS - J.S. Sidikjanov (World Scientific Research Journal, 2025)
Abstract: This article provides a concise analysis of the current state, types, and styles of men’s shirts, as well as an overview of the most popular cuts and design elements.